Cost‐effectiveness of statins for primary prevention of atherosclerotic cardiovascular disease among people living with HIV in the United States. Issue 3 (21st March 2021) - Boettiger, David C; Newall, Anthony T; Phillips, Andrew; Bendavid, Eran; Law, Matthew G; Ryom, Lene; Reiss, Peter; Mocroft, Amanda; Bonnet, Fabrice; Weber, Rainer; El‐Sadr, Wafaa; d'Arminio Monforte, Antonella; et al.
Abstract: Background: Expanding statin use may help to alleviate the excess burden of atherosclerotic cardiovascular disease in people living with HIV (PLHIV). Pravastatin and pitavastatin are preferred agents due to their lack of substantial interaction with antiretroviral therapy. We aimed to evaluate the cost‐effectiveness of pravastatin and pitavastatin for the primary prevention of atherosclerotic cardiovascular disease among PLHIV in the United States. Methods: We developed a microsimulation model that randomly selected (with replacement) individuals from the Data‐collection on Adverse Effects of Anti‐HIV Drugs study with follow‐up between 2013 and 2016. Our study population was PLHIV aged 40 to 75 years, stable on antiretroviral therapy, and not currently using lipid‐lowering therapy. Direct medical costs and quality‐adjusted life‐years (QALYs) were assigned in annual cycles and discounted at 3% per year. We assumed a willingness‐to‐pay threshold of $100, 000/QALY gained. The interventions assessed were as follows: (1) treating no one with statins; (2) treating everyone with generic pravastatin 40 mg/day (drug cost $236/year) and (3) treating everyone with branded pitavastatin 4 mg/day (drug cost $2, 828/year). The model simulated each individual's probability of experiencing atherosclerotic cardiovascular disease over 20 years. Results: Persons receiving pravastatin accrued 0.024 additional QALYs compared with those not receiving a statin, at an incremental cost of $1338, giving an incremental cost‐effectiveness ratio of $56, 000/QALY gained. Individuals receiving pitavastatin accumulated 0.013 additional QALYs compared with those using pravastatin, at an additional cost of $18, 251, giving an incremental cost‐effectiveness ratio of $1, 444, 000/QALY gained. These findings were most sensitive to the pill burden associated with daily statin administration, statin costs, statin efficacy and baseline atherosclerotic cardiovascular disease risk. In probabilistic sensitivity analysis, no statin was optimal in 5.2% of simulations, pravastatin was optimal in 94.8% of simulations and pitavastatin was never optimal. Conclusions: Pravastatin was projected to be cost‐effective compared with no statin. With substantial price reduction, pitavastatin may be cost‐effective compared with pravastatin. These findings bode well for the expanded use of statins among PLHIV in the United States. To gain greater confidence in our conclusions it is important to generate strong, HIV‐specific estimates on the efficacy of statins and the quality‐of‐life burden associated with taking an additional daily pill.